First records of the European free-tailed bat Tadarida teniotis (Rafinesque, 1814) in Slovenia - Primož Presetnik; Ali Šalamun (Natura Sloveniae)
An acoustic survey of bats was conducted throughout 2016 on the slopes of the hill Črna griža near Kozina, and from the end of August 2016 to the end of October 2017 on a small Griško polje plateau close to the village of Dolenja vas near Senožeče — both sites are located in the south-west of Slovenia. Echolocation calls of Tadarida teniotis were recorded at both sites. T. teniotis was recorded near Kozina during 11 nights from April to October 2016, but it was rare, with its 38 passes constituting just 0.53% of all bat passes. It was even rarer near Dolenja vas where it was recorded twice only on the hill Veliki Ognjivec — in April and October 2017 — where constituting only 0.0001% of all bat passes. Both sites are located on the northern border of T. teniotis Submediterranean range. T. teniotis is the 31st bat species recorded in Slovenia and the 30th bat species currently living in the country.